The Impact of Colonialism on the Existence of Religions in Bukittinggi - Novi Hendri (Tamaddun, 2021)
This article analyzes why religions other than Islam can enter and develop in Bukittinggi, a small city in the middle of the highlands of West Sumatra, primarily through the influence of colonialism. In Bukittinggi, at first, the Dutch colonial did not see Muslims as opponents. However, then the Dutch colonial political tendencies took a way to destroy any resistance from the local community by destroying the ulama and Muslims' forces and by developing non-Islamic religions as a rival. This article is using a historical approach. This article explores colonial penetration into Bukittinggi, how religious livelihood in Bukittingi before the colonialism, how people in Bukittinggi respond to a religion other than Islam, and how tolerance and religious harmony in Bukittinggi. The results showed that other than aiming for power, the Dutch colonial carried out the spread of Christianity, especially to association groups, as a means of strengthening power. Colonialist policies towards religions contradicted various principles, especially in education. They were starting from restrictions on religious teachers to the content of lessons, teaching permits, and the number of religious education institutions. The thick religion of Islam in Bukittinggi made it difficult for the Dutch colonialists to conquer Bukittinggi.Artikel ini menganalisis alasan kenapa agama-agama selain Islam dapat masuk dan berkembang di Kota Bukittinggi, terutama melalui pengaruh kolonialisme. Pada konteks Kota Bukittinggi, pada awalnya kolonialis Belanda tidak melihat umat Islam sebagai lawan. Namun kemudian kecenderungan politik kolonialis Belanda menempuh cara menghancurkan setiap perlawanan masyarakat lokal dengan menghancurkan kekuatan-kekuatan ulama dan umat Islam, serta dengan mengembangkan agama non Islam sebagai tandingan. Dengan menggunakan pendekatan historis, artikel ini mengeksplor bagaimana proses masuknya kolonialisme ke Bukittinggi; bagaimana agama masyarakat Bukittinggi sebelum masuknya kolonialisme; bagaimana respon masyarakat Bukittinggi terhadap masuknya agama-agama selain Islam; serta bagaimana toleransi dan kerukunan umat beragama di Bukittinggi. Hasil penelitian menunjukkan bahwa di samping tujuan kekuasaan, kolonialis Belanda melakukan penyebaran agama Kristen, terutama kepada kelompok-kelompok asosiasi, sebagai alat mengokohkan kekuasaan. Kebijakan kolonialis terhadap agama-agama, justru bertolak belakang dengan beragam prinsip, khususnya dalam pendidikan. Mulai dari pembatasan guru agama hingga isi pelajaran, izin mengajar, dan jumlah lembaga pendidikan agama. Kentalnya agama Islam di Bukittinggi menjadikan kolonialis Belanda kesulitan dalam menaklukkan Bukittinggi.